PERENCANAAN GEOMETRIK DAN TEBAL PERKERASAN RUNWAY IV BANDAR UDARA SOEKARNO HATTA - Faruqi, Muhammad Rifqi; Darmadi (JURNAL TEKNIK SIPIL-ARSITEKTUR, 2026)
Air transportation is vital for mobility and national development, particularly in Indonesia as an archipelagic state. Soekarno-Hatta International Airport, the busiest in the country, recorded an aircraft movement CAGR of 11% between 2022–2024 and is projected to exceed 1.5 million movements by 2044. To accommodate this growth, the construction of a fourth runway is essential to ensure operational capacity, safety, and efficiency. This study analyzes the geometric design and flexible pavement thickness of Runway IV, referencing ICAO Annex 14, FAA AC 150/5320-6G, and national regulation PR 21/2023. The Boeing 777-300ER was designated as the critical aircraft. Calculations were conducted manually using FAA charts and validated through FAARFIELD simulations, with primary data including aircraft specifications and subgrade CBR values. Results indicate a runway length of 3,600 m and width of 60 m under ARC 4E classification, with shoulders of 10.5 m, a runway strip of 150 m, and RESA dimensions of 240 × 90 m. Pavement thickness requirements were 32 inches (manual) and 33.3 inches (FAARFIELD), both meeting ICAO and FAA standards. Runway markings also comply with ICAO and national regulations. In conclusion, the proposed design of Runway IV meets international and national standards and supports sustainable long-term air traffic growth.